Transgenic tomato (Solanum lycopersicum Mill.) regeneration by comparing different transformation techniques - Datta, Anamika (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Masters of Science in Biotechnology, 2015.